Home-schooling and caring for children during the COVID-19 lockdown in the UK: emotional states, systems of support and coping strategies in working mothers - Kallitsoglou, Angeliki; Topalli, Pamela-Zoe (Frontiers in Sociology, 2024)
Introduction We examined the experience of the intensification of home-schooling and/or childcare in working mothers in the United Kingdom during the first national COVID-19 lockdown. Our focus was on understanding how mothers dealt with this challenging period both emotionally and practically. Methods Eligible mothers (n = 47; Mage = 39.6) participated in an anonymous online survey of openended questions. Results Thematic analysis of responses showed that mothers found home-schooling and/or childcare to be challenging. This was particularly notable in situations where support from partners, schools, and workplaces was limited. For single working mothers, the absence of support resources was especially impactful. Mothers often felt overly stressed trying to balance work and family responsibilities, guilty for not meeting their child’s needs, and were worried over their child’s well-being and academic progress and over increasing work demands. Common strategies mothers used to cope with the challenges of home-schooling and/or childcare included adopting a positive outlook, implementing flexible family structures, increasing family connectedness, and negotiating alternative partnership models. Discussion The intensification of home-schooling and/or childcare during the lockdown in the United Kingdom negatively affected maternal well-being, particularly due to limited support. These findings underscore the importance of prioritizing maternal wellbeing in post-pandemic recovery efforts. Additionally, they highlight the social dimension of maternal wellbeing and suggest a comprehensive approach to support it that includes both timely access to intervention for mental health but also implementing family-friendly work policies and offering support with childcare and children’s learning as essential measures.